2017
DOI: 10.1016/j.tele.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing intention to donate via social network site (SNS): From Asian’s perspective

Abstract: This study examined whether external factors, which are charity project, charity organization, Internet technology features and social network site (SNS) features influence people's general attitude towards online donation and their intention to donate via SNS. An online survey was conducted based on the framework of factors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
5
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(181 citation statements)
references
References 37 publications
9
135
5
10
Order By: Relevance
“…The residual energy of the node is defined as G for all adjacent grid M and N, and update grid coverage, and the new university language teaching is obtained. The distribution control of SNS network platform nodes is obtained as follows: area of the SNS network platform, and R c is the communication radius of the node [15][16][17].…”
Section: Node Coverage Of Sns Network Platformmentioning
confidence: 99%
“…The residual energy of the node is defined as G for all adjacent grid M and N, and update grid coverage, and the new university language teaching is obtained. The distribution control of SNS network platform nodes is obtained as follows: area of the SNS network platform, and R c is the communication radius of the node [15][16][17].…”
Section: Node Coverage Of Sns Network Platformmentioning
confidence: 99%
“…Crowdfunding sites offer a new channel for charitable giving, thereby opening up additional dimensions of factors that affect donation behavior. In a recent study, social network site features are included, together with variables related to project, organization, and trust (Sura, Ahn, & Lee, 2017).…”
Section: Research Backgroundmentioning
confidence: 99%
“…This has helped not only to maintain the experienced blood donors to continuously support the program, but also to recruit the new blood donors. Previous studies also argued that online social media can significantly contributes to influence public towards donation (Sura et al, 2017) and other related health problems (Khan et al, 2017;Rusaert et al, 2014;Gasper et al, 2014). Besides providing public with the knowledge of donating blood, the public also will know about current situation of blood product reserve in our country, whereby it was reported that the current reserve is still inadequate (Kosmo Online, 2018; Ngah, 2017).…”
Section: Intensive Advertisingmentioning
confidence: 90%